EFL Teachers’ Professional Identity: A Narrative Study With Colombian Graduate Students - Jhon Eduardo Mosquera-Pérez; Jhon Jairo Losada-Rivas (Profile: Issues in Teachers' Professional Development)
This paper reports a qualitative narrative study that explored the trajectories of English language teachers’ identities before and after their participation in a master’s program in English language teaching at a Colombian public university. After analyzing the data gathered through oral narratives and narrative interviews, results showed that teachers’ identities are part of an endless process nurtured by experiences at the academic, pedagogical, and personal levels. We found that such experiences were constantly cultivated and analyzed in the master’s seminars, which positively influenced the development of the participants’ identities by making them more reflective and critical practitioners. Most teachers reported developing higher levels of social commitment, critical-reflective engagement, and research-oriented practices due to their graduate academic experience.